Ancient Ethiopian Cosmology: Indigenous Star Lore, Sacred Astronomy, and Celestial Influences on Culture - Belay Sitotaw Goshu; Muhammad Ridwan (Lakhomi Journal Scientific Journal of Culture, 2026)
Ethiopia possesses a rich and diverse legacy of scientific achievements, yet its contributions to early global science remain underrepresented in scholarly narratives. This study examines Ethiopia's historical role in advancing early scientific thought, focusing on astronomy, mathematics, medicine, and engineering. The objective of this study was to investigate Ethiopia's early scientific contributions in these fields, assess their influence on global knowledge and the extent of their marginalization in contemporary academic discourse, and propose strategies for greater recognition and integration into the global history of science. A mixed-methods approach was employed, combining qualitative historical text analysis, interpretation of archaeological evidence, and semi-structured interviews with Ethiopian scholars and historians (Bernard, (2017). These methods were selected for their aptness in addressing the multifaceted nature of historical inquiry: textual analysis and archaeological interpretation provided direct evidence of ancient practices, while interviews offered contemporary expert insights into cultural continuity and scholarly gaps. Quantitative statistical analysis was additionally applied to compare the significance and scope of Ethiopia's contributions with those of other ancient civilizations (e.g., through metrics such as documented innovations and chronological parallels), thereby validating qualitative findings with empirical rigor. Results revealed substantial Ethiopian advancements, including sophisticated astronomical knowledge embodied in the Ge'ez calendar, extensive ethnobotanical expertise in medicine with numerous indigenous plants identified for therapeutic uses, and remarkable engineering feats exemplified by the rock-hewn churches of Lalibela, which influenced durable construction techniques. However, these contributions have been systematically marginalized in global scientific histories. In conclusion, reclaiming Ethiopia's intellectual heritage is essential for a more inclusive and accurate narrative of scientific development. Recommendations include digitizing ancient Ethiopian scientific manuscripts, incorporating these achievements into international curricula, promoting collaborative research initiatives, and enhancing public awareness campaigns.